The Duty And Authority Of Regional Notary Supervisory Board Regarding Reports From The Public On Alleged Violations Of The Code Of Conducts - Margo Hadi Pura; Maharani Nurdin (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
The notary is a public official who is authorized to make an authentic deed and has other authorities as referred to in the laws. This regulation is stated in Article 1 point 1 of Act No. 2/2014 on the Amendments to Act No. 30/2004 on the Notary (hereinafter referred to as the Notary Act). In the provisions of the Notary Act, there were many changes regarding the authority of the Regional Notary Supervisory Board in supervising and fostering Notaries. The task of the Regional Notary Supervisory Board is to supervise Notaries as referred to in the Notary Act and the Minister of Law and Human Rights Regulation No. M.02.PR.08.10 of 2004 on Procedures for Appointing Members, Dismissing Members, Organizational Structure, Work Procedures, and Audit Procedures. The Regional Notary Supervisor Board has the authority to carry out supervision according to Notary Act, In the provisions of Article 1 point 3 of the Minister of Law and Human Rights Regulation No. 15/2020 on Procedures for Examination of the Supervisory Council Against Notaries which stipulates that a report is a complaint from the public as a party who is harmed due to the behavior and/or implementation of the position of a Notary, as well as reports originating from the exercise of the authority of the Supervisory Board.